A brief presentation of The Oxford Handbook of Belgian Politics - Reuchamps, Min; Brans, Marleen; Meier, Petra; van Haute, Emilie (Politics of the Low Countries, 2025)
While the idea of a comprehensive volume on Belgian politics, in English, had been floating for quite some time among political scientists in Belgium, the spark for this Handbook of Belgian Politics came from our neighbours to the North. Indeed, when we heard that a Handbook of Dutch Politics was in preparation (‘t Hart et al., 2024), we immediately thought: why not Belgium?